Non-traumatic chylothorax: diagnostic and therapeutic strategies. Issue 2 (9th August 2022) - Ur Rehman, Khalil; Sivakumar, Parthipan
Non-traumatic chylothorax refers to accumulation of chyle in the pleural space in the absence of any traumatic disruption to the thoracic duct. Chyle originates from the intestines and is transported via the thoracic duct into systemic circulation. The anatomical course of the thoracic duct is complex with considerable variation; therefore, development of chylothorax is dependent on the site and level of the thoracic duct defect. Non-traumatic chylothorax is associated with a wide range of medical disorders, but malignancy accounts for three-quarters of cases. In up to 9% of cases, the aetiology remains unknown (termed idiopathic chylothorax). Gross appearance of pleural fluid is neither sensitive nor specific enough to diagnose chylothorax; therefore, biochemical analysis of the pleural fluid is required. Pleural fluid triglyceride level >1.24 mmol·L −1 (110 mg·dL −1 ) with a cholesterol level <5.18 mmol·L −1 (200 mg·dL −1 ) is diagnostic of chylothorax. In borderline cases, lipoprotein electrophoresis can help confirm the diagnosis by detecting chylomicrons in the pleural fluid. Once the diagnosis of chylothorax is confirmed, the next step is to find the cause and identify the leakage point, for which various lymphatic specific radiological investigations may have an important role. There is paucity of data on the most suitable approach to manage non-traumatic chylothoraces and treatment often depends on the underlying cause. In general, conservative treatment is tried first, usually for a limited time, before considering more invasive measures. A multidisciplinary approach is recommended with close liaison among the respiratory physicians, thoracic surgeons, oncologists, interventional radiologists, dietitians and pharmacists. Educational aims: To review the pathophysiology, aetiology, and epidemiology of non-traumatic chylothorax. To discuss diagnostic and therapeutic strategies in the management of non-traumatic chylothorax. Non-traumatic chylothorax is associated with a myriad of medical disorders. Lipid analysis of pleural fluid is required to confirm the diagnosis. A multidisciplinary approach is recommended for the effective management of non-traumatic chylothorax. https://bit.ly/3Nssb7n